Relation between Kidney Length and Cardiovascular and Renal Risk in High-Risk Patients - van der Sande, Nicolette G.C. (Clin J Am Soc Nephrol, 2017)
BACKGROUND AND OBJECTIVES: Kidney length is often measured during routine abdominal ultrasonography and may be of use to identify patients at high vascular and renal risk. We aimed to explore patient characteristics related to kidney length, from which reference values were derived, and evaluate the relationship between kidney length and the risk of cardiovascular events and ESRD in high-risk patients. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: The study population consisted of 10,251 patients with clinical manifest arterial disease or vascular risk factors included in the Second Manifestations of ARTerial disease (SMART) Study cohort between 1996 and 2014. Linear regression was used to explore patient characteristics of kidney length. The relationship between kidney length and cardiovascular events (myocardial infarction, stroke, and cardiovascular mortality), all-cause mortality, and ESRD was analyzed using Cox regression. Kidney length was analyzed in tertiles, using the second tertile as the reference category. RESULTS: Kidney length was strongly correlated with body surface area (2.04 mm; 95% confidence interval [95% CI], 1.95 to 2.13 per 0.1 m(2) increase) and eGFR (1.62 mm; 95% CI, 1.52 to 1.73 per 10 ml/min per 1.73 m(2) increase). During the median follow-up of 6.3 years, 1317 patients experienced a cardiovascular event, including 711 myocardial infarctions, 369 strokes, and 735 vascular cause deaths. A total of 1462 patients died of any cause and 52 patients developed ESRD. Irrespective of eGFR, patients in the third tertile of kidney length (11.7–16.1 cm) were at higher risk of cardiovascular mortality (hazard ratio, 1.33; 95% CI, 1.05 to 1.67) and cardiovascular events (hazard ratio, 1.28; 95% CI, 1.09 to 1.50). Patients in the first tertile of kidney length (7.8–10.8 cm) were not at higher risk of cardiovascular adverse events. CONCLUSIONS: Large kidney length is related to higher risk of cardiovascular events and mortality in high-risk patients, irrespective of eGFR. Kidney length may serve as a clinical marker to further identify patients at high cardiovascular risk.